Studi mengenai kepuasan pasien rawat inap di Jawa Tengah - Bramasta, Arya Adi; Keni, Keni (Universitas Tarumanagara, 2024)
This study aims to analyze the influence of the variables of patient-physician relation, hospital image, and word of mouth on inpatient satisfaction at a hospital in Central Java. This research is descriptive with a cross-sectional approach. The total sample size for this study consisted of 160 inpatients at a hospital in Central Java. Based on the research findings, it was found that patient-physician relation has a positive and significant impact on inpatient satisfaction at hospital in Central Java. Hospital image also has a positive and significant impact on inpatient satisfaction at hospital in Central Java. Word of mouth likewise has a positive and significant influence on inpatient satisfaction at hospital in Central Java. The research result hopefully can become literacy material for further research, especially in the field of health services, and as a reference and evaluation material to improve hospital services, so that patients feel satisfied with the services provided. Penelitian ini bertujuan untuk menganalisis pengaruh variabel patient-physician relation, hospital image, dan word of mouth terhadap patient satisfaction rawat inap pada rumah sakit di Jawa Tengah. Jenis penelitian ini deskriptif dengan pendekatan cross-sectional. Jumlah sampel penelitian ini sebanyak 160 pasien rawat inap pada rumah sakit di Jawa Tengah. Berdasarkan hasil penelitian, ditemukan patient-physician relation berpengaruh positif dan signifikan terhadap patient satisfaction rawat inap pada rumah sakit di Jawa Tengah. Hospital image berpengaruh positif dan signifikan terhadap patient satisfaction rawat inap pada rumah sakit di Jawa Tengah. Word of mouth berpengaruh positif dan signifikan terhadap patient satisfaction rawat inap pada rumah sakit di Jawa Tengah. Hasil penelitian ini diharapkan dapat menjadi bahan literasi untuk penelitian selanjutnya, khususnya pada bidang layanan kesehatan dan sebagai acuan serta bahan evaluasi untuk meningkatkan layanan rumah sakit, sehingga pasien merasa puas terhadap layanan yang diberikan.